CARA MENCEGAH KERUSAKAN GIGI DAN PENANGGULANGAN GIGI BERLUBANG DALAM RANGKA MENINGKATKAN KUALITAS HIDUP - Kisworo Utami, Naning; Amperawati, Metty; Nurwati, Bunga; Rahmawati , Nur; Azzahra, Irhaminnisa; Akbar, Muhammad Fadhil (UPPM Poltekkes Kemenkes Banjarmasin, 2023)
Dental and oral health is still something that needs to be considered, based on Basic Health Research (Riskesdas) in 2018 shows that the proportion of Indonesians who have dental caries problems in the age group of 5-9 years is 92.6% and the age of 10-14 years is 73.4%. The prevalence of caries in South Kalimantan province is 46.9%. Although dental caries is a disease that must be prevented, it remains the main chronic disease in children aged 6-11 years (25%) and adolescents aged 12-19 years (59%). The purpose of community service is to do: a) Counseling on how to brush your teeth properly and correctly, b) measurement of saliva pH, c). triplak application, d). mass brush activities, e). check OHI-S, f). Identify DMF-T, and g). ART patching for orphanage children and students of MTS Muhammadyah Martapura, Banjar Regency, South Kalimantan Province.The target of community service for orphanage children and MTS Muhammadyah students is 64 people. Activities include promotive, preventive and simple curative. Place, in the women's orphanage and MTS Muhammadyah Martapura, Banjar Regency, South Kalimantan Province. Tools and materials used dental phantom, diagnostic tool set, cotton swab, tissue, mask, gloves, soap, alcohol, nier beken, agate spatel, aqua glass, toothbrush and toothpaste, Advantec test paper / saliva pH indicator, sunken mica, Fuji IX, and examination format and writing stationery.The results of counseling 90% of children are not aware about how to brush their teeth correctly, normal salivary pH measurements, Most of the plaque appears on the surface of their teeth, OHI-S measurement = 1.52, bulk toothbrushes are carried out according to counseling, the examination obtained an average DMF-T number of 4.03 where the average child has 4 tooth holes in each student above the average National DMF-T number ≤ 1, and cannot be filled because the tooth hole is large and deep. In conclusion, the average DMF-T number is high, salivary pH is normal and OHI-S is recommended to carry out cavity treatment and tartar cleaning at the health center / hospital so that the tooth decay process does not continue.